Analysis of Dynamical Characteristic of Piecewise-Nonlinear Asymmetric Hysteretic System Based on Incremental Harmonic Balance Method - H. R. Liu; J. Z. Li; D. X. Hou; R. R. Yin; J. S. Jiang (Discrete Dynamics in Nature and Society)
Considering a sort of elastic mass with asymmetric hysteresis characteristic which widespread existing in engineering field, a piecewise-nonlinear dynamical equation, which contains asymmetric hysteretic loop, is established. By using the method of Incremental Harmonic Balance (IHB), the analytic linearized algebraic equation of the system is obtained. On the basis of this algebraic equation, the coefficients of the algebraic expression are figured out by the incremental procedure and the iterative process of the regulated variable. Through the emulation, the amplitude frequency response curve and the relation between the value of the harmonic component and the external excitation are researched; the bistable regions of the bifurcation diagram of the system under the variation of the excitation amplitude are studied. The above results can be used to guide the research of the asymmetric hysteretic system with polynomial expression.